Stable Frequencies of HLA-C*03:04/Peptide-Binding KIR2DL2/3+ Natural Killer Cells Following Vaccination - Ziegler, Maja Christiane; Grañana, Ferran Borràs; Garcia-Beltran, Wilfredo F.; Schulze zur Wiesch, Julian; Hoffmann, Christian; Rechtien, Anne; Lunemann, Sebastian; Altfeld, Marcus (Frontiers in Immunology, 2018)
Inhibitory KIRs play a central role in regulating NK cell activity. KIR2DL2/3 bind to HLA-C molecules, but the modulation of these interactions by viral infections and presentation of viral epitopes by HLA-C molecules is not well-understood. We investigated whether the frequencies of KIR2DL2/3+ NK cells recognizing HLA-C*03:04/viral peptide complexes were impacted by YFV vaccination or HIV-1 and HCV infection. Ex vivo HLA-I tetramer staining of primary human NK cells derived from YFV-vaccinated individuals, or HIV-1- or HCV-infected individuals revealed that YFV/HLA-C*03:04-NS2A4-13-tetramers bound to the largest proportion of KIR2DL2/3+ NK cells compared to HIV-1/HLA-C03:04-Gag2096-304- or HCV/HLA-C*03:04-Core136-144-tetramers. The YFV/HLA-C*03:04-NS2A4-13-tetramer also exhibited a stronger avidity to KIR2DL2/3 compared to the other tested tetramers. The proportional frequencies of KIR2DL2/3+ NK cells binding to the three tested HLA-C*03:04 tetramers were identical between YFV-vaccinated individuals or HIV-1- or HCV-infected individuals, and remained stable following YFV vaccination. These data demonstrate consistent hierarchies in the frequency of primary KIR2DL2/3+ NK cells binding HLA-C*03:04/peptide complexes that were determined by the HLA-C-presented peptide and not modulated by the underlying viral infection or vaccination.